Development of Functional Collagen Cubes From Chicken Legs and Mint Leaves - J. Naser, Mokhtar; A. Mjed, Hussam; A.Shkeir, Zainab; ALmaamori, Teeb A.; Huwaidi, Heba B.; Alshemari, Nada A.; Al-Salhi, Ahmed A.; Al-Shatty, Sabah M. (Health & Medical Sciences, 2025)
This study aimed to investigate the effect of adding aqueous Mentha sp. (mint) leaf extract at different concentrations (1%, 2%, and 3%) on the properties of collagen cubes extracted from chicken feet. Collagen was obtained from chicken feet and used to produce functional cubes enriched with natural mint extract. The results revealed that the addition of mint extract significantly improved the sensory attributes of the collagen cubes, particularly flavor, juiciness, texture, and overall acceptability. Among all treatments, the sample containing 2% mint extract (T3) achieved the highest scores (p < 0.05), indicating that this concentration provided the most desirable balance between firmness, flavor intensity, and consumer preference. The improvement is mainly attributed to the phenolic and antioxidant compounds present in Mentha sp., which enhance water retention, stabilize the collagen network, and minimize undesirable odors that may develop during processing or storage. However, increasing the extract concentration to 3% slightly reduced acceptability due to the strong herbal flavor dominating the product. These findings suggest that moderate incorporation of Mentha sp. extract (2%) into chicken feet collagen cubes can enhance product quality and sensory appeal, providing a promising approach for developing innovative, natural, and health-promoting collagen-based functional foods.